Understanding and Modeling Förster-type Resonance Energy Transfer (FRET) FRET from Single Donor to Single Acceptor and Assemblies of Acceptors, Vol. 2 - Hernández Martínez, Pedro Ludwig; Govorov, Alexander; Demir, Hilmi Volkan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This Brief presents a complete study of the generalized theory of Förster-type energy transfer in nanostructures with mixed dimensionality. Here the aim is to obtain a generalized theory of FRET including a comprehensive set of analytical equations for all combinations and configurations of nanostructures and deriving generic expressions for the dimensionality involved. In this brief, the modification of FRET mechanism with respect to the nanostructure serving as the donor vs. the acceptor will be included, focusing on the rate's distance dependency and the role of the effective dielectric function in FRET, which will be a unique, useful source for those who study and model FRET.
FRET models -- Electric potential and effective dielectric medium of nanostructure geometries -- Energy transfer theory -- Nonradiative energy transfer in single nanostructures (item-to-item) -- Summary -- Appendix.
Keywords: Microtechnology; Microelectromechanical systems; Nanoscience; Nanotechnology; Electrical engineering; Electric power production; Microsystems and MEMS; Nanophysics; Nanotechnology; Electrical and Electronic Engineering; Electrical Power Engineering; Mechanical Power Engineering